Technologies of Interpretation: Design and Redesign of the Tahitian Marketplace at the Field Museum of Natural History - Jones, Laura (Anthropologica, 2022)
Museum exhibitions are a special genre of anthropological communication: one that offers unique creative opportunities for the practice of applied anthropology. This paper tells the story of one controversial exhibition and offers some lessons learned from the experience. Museums stand at a critical crossroads where innovation and risk taking can lead to anew age of museum participation in popular education and cultural enrichment. The author encourages museums to abandon the trend towards expensive and time-consuming renovations of outdated permanent exhibitions (they will always be out of date), and to look instead towards new technologies and approaches that allow a wider range of educators and artists to create more temporary exhibitions.